Family Functioning of Schizophrenia Patients in the Outpatient Unit of Menur Mental Hospital, East Java Province - A.V. Sri Suhardiningsih; Dya Sustrami; Ah. Yusuf; Rizki Fitriyasari (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2023)
The phenomenon of a family caregiver caring for family members with schizophrenia requires a balance of family functions. Imbalances in family functioning can affect caregivers in caring for schizophrenic patients. The aim of this study was to describe the family function of schizophrenia patients. Methods: The research design used probability sampling with simple random sampling. Data collection using FAD (Family Assessment Device) questionnaires. Using a sample of families caring for family members experiencing schizophrenia that met the inclusion and exclusion criteria with 160 respondents. Results: The result of the study was the family function criteria were found in good family function criteria of as many as 86 people (53.8%). Conclusion: The implication of this study was family function among schizophrenia patients is needed to decrease the family burden.